Solvent free UV curable waterborne polyurethane acrylate coatings with enhanced hydrophobicity induced by a semi interpenetrating polymer network - Ali Reza Banan (Scientific Reports)
Abstract This study presents the synthesis and characterization of solvent-free, UV-curable waterborne polyurethane-acrylate (WPUA) coatings using a semi-interpenetrating polymer network (sIPN) technique, aiming to develop durable, high-performance eco-friendly coatings. The WPUA formulations consisted of a urethane backbone created from polytetrahydrofuran (PTHF) and isophorone diisocyanate (IPDI), combined with urethane dimethacrylate (UDMA) to introduce acrylate functionality. The synthesized coatings were thoroughly analyzed to assess their morphology, thermal stability, spectroscopic characteristics, water absorption, adhesion strength, and mechanical properties. The design of experiments (DoE) approach was applied to optimize film characteristics, particularly tensile strength. Mechanical testing revealed that incorporating UDMA into the WPUA matrix significantly improved tensile strength, increasing from 4.1 MPa to 8.8 MPa in the optimized formulation. The increase in the cross-cut adhesion test rating from 3B to 5B demonstrates that UV curing significantly enhanced adhesion. Furthermore, the addition of UDMA increased hydrophobicity, reducing water absorption and raising the water contact angle from 67° to 83°.These results indicate that the UV-cured WPUA films possess superior mechanical properties, thermal stability, and water resistance, making them viable options for sustainable coating applications.